Proceedings. 2004 International Conference on Information and Communication Technologies: From Theory to Applications, 2004.
DOI: 10.1109/ictta.2004.1307730
|View full text |Cite
|
Sign up to set email alerts
|

Continuous phase modulation for future satellite communication systems in ka band

Abstract: Future satellite communications systems will be characterized by two-way connection between many UT User Terminals and a GEO satellite with On-Board Processing. They will propose different kind of services such as Internet access and interactive multimedia applications. The transmitted data consists of many audio and video contents, so it requires QEF (Quasi-Error-Free) transmission and high bandwidth efficiency. System will operate in Ka-band with MF-TDMA access method on the uplink. Such systems have to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Research has demonstrated that an adaptive waveform is a key factor [13], and because of its constant envelope, CPM signals show high resistance to channel non-linearity and more flexibility than "classic" waveforms to cope with propagation conditions [3].…”
Section: B Research and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has demonstrated that an adaptive waveform is a key factor [13], and because of its constant envelope, CPM signals show high resistance to channel non-linearity and more flexibility than "classic" waveforms to cope with propagation conditions [3].…”
Section: B Research and Developmentmentioning
confidence: 99%
“…Adaptive modulation combined with powerful coding techniques, such as Low Density Parity Check (LDPC) or turbo codes, could improve the availability of the mobile link. Also, the quality of transmission on the link is crucial since Quasi Error Free (QEF) transmission is required to support multimedia applications [1], [3].…”
Section: B Research and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase modulated signals allow on-board coherent demodulation of the received signal. PM signals show high resistance to channel non-linarity thanks to their constant envelope and, moreover, the multiplicity of modulation schemes offer more flexibility to cope with propagation conditions [1].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [19] reported that CPM is a promising solution for future satellite communication systems in the Ka band because it yields a constant envelope signal that enables the nonlinear power amplifier to operate near saturation. From the power efficiency point of view, a serially coded CPM can provide high power gain when the iterative decoding process is performed.…”
Section: Introductionmentioning
confidence: 99%